Incomplete Cross-Resistance to Folpet and Iprodione in Botrytis cinerea from Grapevine in South Africa - Fourie, P.H.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
The sensitivity to folpet of Botrytis cinerea isolates obtained from table grape vineyards in the Western Cape province of South Africa with a known history of dicarboximide (DC) resistance and high-schedule DC and folpet programmes was investigated. In the Simondium vineyards, 61 % of the B. cinerea isolates from Dan-hen-Hannah and 20% of the isolates from Waltham Cross were resistant to iprodione. In the Northern Paarl vineyards, 95% of the isolates from Dan-hen-Hannah and 95% of the isolates from Waltham Cross were designated resistant. In the case of the iprodione-sensitive isolates from vineyards in Simondium, folpet ECso values ranged from 4.9 to 29.1 μg/mL for the Dan-hen-Hannah and 15.0 to 43.5 μg/mL for the Waltham Cross sub-populations, respectively. Folpet ECso values of the iprodione-resistant isolates, on the other hand, ranged from 19.7 to above 100 μg/mL for the Dan-hen-Hannah subpopulation. In the Northern Paarl subpopulations, where the isolates were predominantly iprodione-resistant, folpet ECso values of the latter isolates ranged from 21.5 to above 100 μg/mL. Similar shifts in folpet sensitivity were displayed by ultra-low- and low-level DC-resistant B. cinerea isolates obtained from other regional subpopulations. The results indicated incomplete cross-resistance between iprodione and folpet. This finding suggests that early increases in DC resistance frequencies in B. cinerea, observed prior to DC application in vineyards under the high-schedule DC and folpet programmes, can be attributed to incomplete cross-resistance to these fungicides in sub-populations of the pathogen.